On the cost and delay in obtaining loans on land and the high rate of interest charged to tenants for loans - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1881)
The failure of the potato crop in Ireland, in 1845, which led to Sir Robert Peel's cabinet adopting and carrying Free Trade, was followed by the still more extensive failure in 1846. This brought on a paralysis of credit, and so directed attention to the peculiar inconvenience of our laws with regard to loans on landed security?the delay in making out title.
Read before the Society, 21 December 1880
Keywords: Borrowing; Interest rates; Collateral; Irish tenant farmers; 314.15